'Tchaikovsky is ours:' the practice of minor music from the barrios of Venezuela. Issue 3 (2nd July 2020) - Stainova, Yana
ABSTRACT: How do young people living in social exclusion in Venezuela negotiate their deep personal attachment to classical music and the genre's association with dominant European culture? I approach this topic through my ethnographic fieldwork with young musicians who are members of Venezuela's nation-wide classical music program El Sistema. The majority of these musicians are from the lower social classes in an unequal society deeply divided along the intersecting lines of race, ethnicity, and class. Transposing Deleuze and Guattari's concept of minor literature to music, I propose the notion of 'minor music' to explore the relationship between classical music practices, social exclusion, and aspiration. Minor music sheds light on how people on the margins of society inhabit dominant identities strategically, critically, and by making them 'their own.' Through a focus on the experiences of the young performers, I explore how they may articulate an individual and collective self within and through the medium of dominant categories. This has the simultaneous effect of both reproducing deep-rooted ethno-racial and economic hierarchies, while also infusing dominant identities with contrary forms of creativity and meaning embedded in the musicians' marginal social positions.